2018 European Conference on Donor Health and Management. Issue 1 (11th March 2019) - Cho, G.
Summary: The third European Conference on Donor Health and Management (ECDHM) was held in Copenhagen from 5th to 7th September 2018 and was co‐organised by the ECDHM committees and European Blood Alliance. This is an international conference with a focus on 'donor health', including donors of blood, organs and other substances of human origin, and remains the only conference focusing exclusively on donor medicine. This overview presents a selection of research topics in relation to iron, the keynote speeches and plenary talks. The keynote speeches cover the epidemiology of donors and recipients, whole‐blood donor recruitment and retention and the safety of donors and recipients of plasma and plasma products. Talks from the plenary speakers reviewed modern multi‐omic approaches to study red cell quality and the central, perennial question of what motivates a donor to give blood and how can this be encouraged.